Analysis of Students’ Learning Motivation: Psychometric Parameters Study of Learning English Courses in the Business Travel Department - M Bambang Purwanto; Umar; Moch. Malik Al Firdaus (Metathesis: Journal of English Language, Literature, and Teaching)
This study's goal is to determine the variables that affect students' motivation to learn English at Darussalam Polytechnic Palembang's Travel Business study program. The basis of this research is seen in the weak mastery of English possessed by students of the travel business study program. This study also aims to find specific motivations that best influence learning English. This study used a qualitative method by giving participants a questionnaire consisting of 20 statements and a Likert scale. The sampling technique used is saturated sampling. The data from the questionnaire were analyzed using statistical procedures and described descriptively. The findings of this investigation indicate that external motivational factors have a better contribution than internal motivational factors, and in external motivation, there is the quality of the instructor and teaching materials, which are the most dominant sub-factors for maintaining learning motivation.